2017
DOI: 10.1007/s00294-017-0688-5
|View full text |Cite
|
Sign up to set email alerts
|

Connecting virulence pathways to cell-cycle progression in the fungal pathogen Cryptococcus neoformans

Abstract: Proliferation and host evasion are critical processes to understand at a basic biological level for improving infectious disease treatment options. The human fungal pathogen Cryptococcus neoformans causes fungal meningitis in immunocompromised individuals by proliferating in cerebrospinal fluid. Current antifungal drugs target “virulence factors” for disease, such as components of the cell wall and polysaccharide capsule in C. neoformans. However, mechanistic links between virulence pathways and the cell cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 87 publications
(105 reference statements)
1
12
0
Order By: Relevance
“…As cell division is linked to the cell cycle, we evaluated whether cells lacking NCS1 displayed defects in cell cycle regulation by measuring the levels of two transcripts associated with different stages of the cell cycle: the G 1 cyclin encoded by CNL1 ( 52 ) and the S phase DNA replication licensing factor encoded by MCM2 ( 53 , 54 ). We also measured the transcript levels of the G protein-coupled receptor encoded by GPA2 , which displays oscillatory expression during the cell cycle ( 53 , 54 ). All three genes were upregulated in the ncs1Δ strain compared to the WT after 4 h of growth in YPD ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As cell division is linked to the cell cycle, we evaluated whether cells lacking NCS1 displayed defects in cell cycle regulation by measuring the levels of two transcripts associated with different stages of the cell cycle: the G 1 cyclin encoded by CNL1 ( 52 ) and the S phase DNA replication licensing factor encoded by MCM2 ( 53 , 54 ). We also measured the transcript levels of the G protein-coupled receptor encoded by GPA2 , which displays oscillatory expression during the cell cycle ( 53 , 54 ). All three genes were upregulated in the ncs1Δ strain compared to the WT after 4 h of growth in YPD ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given that expression of ∼40 virulence-associated genes is linked to the cell cycle in C. neoformans , the control of this process is fundamental to disease progression ( 53 ). In S. cerevisiae , Ca 2+ homeostasis is linked to cell cycle regulation, as a decrease in intracellular Ca 2+ leads to transient arrest in the G 1 phase, followed by interruption in the G 2 /M phase ( 27 , 56 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…The site of bud formation requires extensive cell wall remodeling and synthesis for the emergence and generation of the daughter cell, and chitin synthesis is required for primary septum formation between mother and daughter cells. Thus, the cell wall synthesis genes are expressed differentially throughout the cell cycle ( 39 , 40 ) and the cell wall integrity pathway is activated at a distinct point during the cell cycle ( 41 , 42 ). The mammalian kinome studies of PIK-75 identified CDK7, CDK9, and CDK14 as targets of PIK-75 ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that expression of ~40 virulence-associated genes is linked to the cell cycle in C. neoformans, the control of this process is fundamental to disease progression (51). In S. cerevisiae, Ca 2+ homeostasis is linked to cell cycle regulation as a decrease in intracellular Ca 2+ leads to transient arrest in the G1 phase, followed by interruption in the G2/M phase (27,(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…As cell division is linked to the cell cycle, we evaluated whether cells lacking NCS1 displayed defects in cell cycle regulation by measuring the levels of two transcripts associated with different stages of the cell cycle: the G1 cyclin encoded by CNL1 (50) and the S phase DNA replication licensing factor encoded by MCM2 (51,52).…”
Section: Ncs1 Is Important For the Release Of Daughter Cells Microscmentioning
confidence: 99%